Study on Heat Wave Penetration into Sandy Soil of Jobner (Rajasthan) - Yadav, M R; Saxena, G S (Annals of Arid Zone, 2016)
A field experiment was conducted to study diurnal variations of temperature in the soil profile both in cropped and bare fields. Attempts were also made to calculate some of the thermal characteristics of the soil (e.g. thermal diffusivity, thermal conductivity) from the phase shift between temperature waves at different depths. Diurnal variations in temperature at any depth were found to be approximately sinusoidal and suffered damping with depth. The amplitude of temperature wave at the surface of the bare soil was as high as 17Â°C, which progressively reduced to only 2Â°C at a depth of 30 cm. The crop only reduced the amplitude but not the damping pattern of temperature which was m1inly governed by moisture content and soil characteristics. Temperature variations were negligible below 30 cm depth both in cropped and bare field.